Narrativas de mujeres en torno a su experiencia de no maternidad: resistencias ante tecnologías de género - Gómez Cruz, Brenda Magali; Guerrero, Olivia Tena (El Colegio de México A.C., 2018)
This article displays the narratives of 11 Mexican middle-aged women regarding their experience of non-motherhood and analyses the different ways in which they resist gender technologies that contribute to the configuration of the binomial woman=mother present in fields such as science (medicine and psychology), the education system and mass media. For this purpose, a qualitative methodology was used with a biographicalnarrative design. The results show that the different ways of resistance practiced by these women have in common the questioning of the knowledge that has been socially normalized. The article concludes that the approach to resistance practices will help to denaturalize the idea of motherhood, to depathologize and resignify non-motherhood, and to dismantle the binomial woman=mother.